Language Use by Polish Immigrants in Iceland: English or Icelandic? - Zaorska, Katarzyna Dorota, 1989- (2012)
The population of Iceland is becoming more culturally and linguistically diverse, and Poles constitute the largest of the national minorities in the country. The goal of this study was to examine the patterns of language use of Poles in Iceland, and how much English and/or Icelandic they speak - including whether this usage varies by gender, age, education and an individuals´ intended length of residence in Iceland. The data was gathered by the means of 33 surveys (conducted in the form of an interview) of 17 women and 16 men. The findings indicated that English is used more often than Icelandic by Polish residents of Iceland, and that the English language is also believed to be more useful than Icelandic. The results also suggest that the English language is more prevalent than Icelandic in terms of its daily use for many Poles in Iceland - for activities such as working, shopping or socializing, and at also that the English language is being acquired by many Poles prior to Icelandic because of its regular use and high exposure in Iceland.